2013
DOI: 10.1111/1754-9485.12062
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic colonography (CTC); colorectal cancer diagnosis with CTC in an Auckland population

Abstract: The sensitivity of 95% for CTC in the detection of colorectal cancer compares favourably with the published national and international data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“…Studies around the world have shown approximately 50% of CTCs having extra‐colonic findings, with increased frequency for older population, and our finding confirms this. More importantly we found that 9.9% of CTCs led to further follow up for potentially important extra‐colonic findings which is comparable with the reported rates in the literature ranging from 6–16% …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies around the world have shown approximately 50% of CTCs having extra‐colonic findings, with increased frequency for older population, and our finding confirms this. More importantly we found that 9.9% of CTCs led to further follow up for potentially important extra‐colonic findings which is comparable with the reported rates in the literature ranging from 6–16% …”
Section: Discussionsupporting
confidence: 90%
“…The referral rate from CTC to colonoscopy in this symptomatic cohort was 16.9% which is higher than the estimated rates of 10.7% and 11.5% reported in other studies . This can be attributed to actual high cancer or polyp prevalence in this study population but also contributed by moderate number of extra referrals for false positive medium sized polyps.…”
Section: Discussioncontrasting
confidence: 68%
“…Characteristics of included studies 30,31,[33][34][35][36][37][38][39][40][41][42] are shown in table 1. Most were retrospective (nine studies 33,[35][36][37][38][39][40][41][42] ) and done at a single centre (nine studies 33,[35][36][37][38][39][40]42 38 all patients with post-test colorectal cancer were included, rather than only those having CT colonography. The sex and age range of included patients was only reported in seven (58%) of 12 studies; 30,31,35,36,[38][39][40] CT colonography technique was inconsistently reported (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Interpretation method was via two-dimensional display with three-dimensional images as necessary in eight (67%) of 12 studies, 30,31,[33][34][35]37,39,40 two-dimensional review alone in one (8%) of 12 studies, 42 and was unreported in three (25%) of 12 studies. 36,38,41 Use of computer-aided detection was not stated in seven (58%) of 12 studies, 33,34,36,38,39,41,42 two (17%) studies 37,40 used it routinely, and in three (25%) studies 30,31,35 it was optional. Five (42%) of 12 studies 33,34,36,37,40 used the C-RADS reporting scheme (6 mm polyp reporting threshold), one (8%) study 35 used a modified C-RADS scheme (also with a 6 mm threshold), two (17%) studies 39,41 used a 10 mm threshold, two (17%) studies 30,31 allowed radiologists to follow their routine clinical practice, and two (17%) studies 38,42 did not detail the reporting threshold used.…”
Section: Resultsmentioning
confidence: 99%
“…There are few data detailing the usage of C-RADS in the clinical screening setting since it was proposed in 2005. Only recently have such programmatic measures been reported in smaller single-institution series [16]. This study represents the results of a 7-year clinical CTC screening experience where C-RADS was prospectively applied to over 7000 patients.…”
Section: Discussionmentioning
confidence: 99%